Nursing care in the face of cardiorespiratory arrest in the emergency sector: An experience report (Research, Society and Development, 2021)
Objective: Cardiopulmonary Arrest (CPA) is an abrupt cessation of cardiac, respiratory and brain function, in this sense, the work aims to show the importance of nursing care in front of Cardiopulmonary Arrest (CPA), in addition to the main care actions of nursing to the patient victim of CPA in a hospital unit in a city in the interior of Bahia. Method: This is a descriptive study of an experience report type about the experience in Supervised Internship II, on the role of nurses during cardiac arrest in the city of Irecê-BA. Results: In this sense, it was possible to observe the role of nurses in nursing care in the face of cardiorespiratory arrest, it was also possible to show that the nurse, through their care, is an essential and capable professional to diagnose and attend to CPA, both in decision-making to start care, as in medication care. Conclusion: The nurse is of paramount importance in the face of a CPA, as a professional active in decision-making and able to identify and carry out the necessary procedures to increase patient survival.